STUDIES ON REMOVAL OF TURBIDITY AND TDS FROM AQUEOUS SOLUTION BY USING EMBLICA OFFICINALIS AND CANNABIS SATIVA LEAF POWDER - Monika Singha , Brij Kishorb (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Water is a vital natural resource that occurs on the earth. In many places having fresh and clean water is a crucial issue. This study focuses on the removal of turbidity and total dissolved solids from aqueous using Emblica Officinalis and Cannabis Sativa Leaf Powder. The results were found that turbidity removal increases with an increase in pH value with different dosage and concentration. However, the percentage of removal of total dissolved solids starts decreasing after a certain pH i.e. at pH 9 for individual experiments and pH7 for combined